Effects of Hydrophilic Carriers on Structural Transitions and In Vitro Properties of Solid Self-Microemulsifying Drug Delivery Systems - Tao Yi; Jifen Zhang (MDPI AG, 2019)
Self-microemulsifying drug delivery systems (SMEDDS) offer potential for improving the oral bioavailability of poorly water-soluble drugs. However, their susceptibilities during long term storage and in vivo precipitation issues limit their successful commercial application. To overcome these limitations, SMEDDS can be solidified with solid carriers, thus producing solid self-microemulsifying drug delivery systems (S-SMEDDS). In this study, effects of various hydrophilic carriers on structural transitions and in vitro properties of S-SMEDDS were investigated in order to set up in vitro methods for screening out appropriate carriers for S-SMEDDS. Liquid SMEDDS was prepared and characterized using nimodipine as a model drug. The effects of various hydrophilic carriers on internal microstructure and solubilization of SMEDDS were investigated by conductivity measurement and in vitro dispersion test. The results showed that hydrophilic carriers including dextran 40, maltodextrin and PVP K30 seemed to delay the percolation transition of SMEDDS, allowing it to maintain a microstructure that was more conducive to drug dissolution, thus significantly increasing the solubilization of nimodipine in the self-microemulsifying system and decreasing drug precipitation when dispersed in simulated gastric fluid. S-SMEDDS of nimodipine were prepared by using spray drying with hydrophilic carriers. The effects of various hydrophilic carriers on in vitro properties of S-SMEDDS were investigated by using SEM, DSC, PXRD and in vitro dissolution. The results showed that properties of hydrophilic carriers, especially relative molecular mass of carriers, had obvious influences on surface morphologies of S-SMEDDS, reconstitution of microemulsion and physical state of nimodipine in S-SMEDDS. Considering that in vitro properties of S-SMEDDS are closely related to their pharmacokinetic properties in vivo, the simple and economical in vitro evaluation methods established in this paper can be used to screen solid carriers of S-SMEDDS well.